Aktivitas Dakwah Gerakan Pemuda (GP) Ansor Dalam Meningkatkan Ukhuwah Islamiyah Di Kecamatan Purbolinggo - Alwanul Fikri (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2022)
Da'wah activity is an activity or effort carried out by humans, organizations or institutions to achieve their daily needs. Activities such as studying, attending school, participating in scientific assemblies, discussions, and other activities are examples of human needs. The Ansor Youth Movement (GP) is a youth, community, and religious organization with a populist character. The Ansor Youth Movement is an autonomous body under the auspices of Nahdlatul Ulama (NU). The Ansor Youth Movement (GP) is not only trying to build and create a society that has an understanding of the Islamic faith, but the Ansor Youth Movement (GP) is also trying to increase ukhuwah Islamiyah between fellow human beings. The purpose of this study was to determine the da'wah activities of the Ansor Youth Movement (GP) in increasing ukhuwah Islamiyah in Purbolinggo District. This research is a field research (Field Research) and the nature of this research is descriptive. The collection method used is observation, interviews and documentation.